Importance of bodyweight at lambing on pre-weaning performance of Pelibuey lambs - Hinojosa-Cuéllar, José Alfonso (2020)
The aim of this study was to evaluate the influence of Pelibuey ewe bodyweight at lambing on pre-weaning performance of their lambs in hot and humid conditions. The study was retrospective and was carried out with productive information on two sheep farms. In total, 242 records of lambs from farm 1 and 66 from farm 2 were analysed for birth weight, pre-weaning bodyweight gain and weaning weight adjusted to 61 days. The information was obtained from 147 ewes on the farm 1 and 42 on the farm 2. The statistical model included, in both farms, the fixed effects of ewe bodyweight at lambing (below and above the average), parity number (primiparous, multiparous), sex of the lamb (female and male) and type of birth (single and multiple). The body weight at lambing and type of lambing affected (p<0.05) all the dependent variables on both farms. The sex of the lamb only affected (p<0.05) the weaning weight in farm 1. Parity number influenced birth and weaning weight in farm 1 (p<0.01) and birth weight in farm 2 (p<0.05). In conclusion, the ewe bodyweight at lambing affected the pre-weaning performance of lambs in both farms. Lambs of ewes with a bodyweight al lambing above average were heavier at birth and at weaning than sheep from ewes with bodyweight al lambing below average, and it is confirmed that male lambs, single lambs and from multiparous sheep they better pre-weaning performance with respect to female, multiple lambs and those of primiparous sheep, respectively.